Macroscopic Innervation of the Dura Mater Covering the Middle Cranial Fossa in Humans Correlated to Neurovascular Headache - Lee, Shin-Hyo; Hwang, Seung-Jun; Koh, Ki-Seok; Song, Wu-Chul; Han, Sang-Don (Frontiers in Neuroanatomy, 2017)
The trigeminovascular system within the cranial dura mater is a possible cause of headaches. The aim of this study is to investigate macroscopically dural innervation around the middle meningeal artery (MMA) in the middle cranial fossa. 44 sides of the cranial dura overlying the skull base obtained from 24 human cadavers were stained using Sihler’s method. Overall, the nervus spinosus (NS) from either the maxillary or mandibular trigeminal divisions ran along the lateral wall of the middle meningeal vein rather than that of the MMA. Distinct bundles of the NS running along the course of the frontal branches of the MMA were present in 81.8% of cases (N = 36). Others did not form dominant nerve bundles, instead giving off free nerve endings along the course of the MMA or dural connective tissue. The distribution of these nerve endings was similar to that of the course of the frontal, parietal, and petrosal branches of the MMA (11.4%). The others were not restricted to a perivascular plexus, crossing the dural connective tissues far from the MMA (6.8%). These findings indicate that the NS generally travels alongside the course of the frontal branches of the MMA and terminates in the vicinity of the pterion.